S66 Deletion of mesenchymal Gαq/11 results in abnormal lung development and renal abnormalities: a transgenic mouse study. (December 2018) - Goodwin, AT; John, AE; Habgood, A; Tatler, AL; May, ST; Castellanos, M; Susztak, K; Palmer, M; Henderson, NC; Offermanns, S; Jenkins, G
Abstract : Background: Developmental lung diseases cause significant mortality and lifelong morbidity. There is no treatment to restore normal organogenesis, but research into the molecular mechanisms of lung development may identify therapeutic targets. Normal lung development requires the coordinated activity of numerous cell types, and has shared signalling pathways with neoplasia. Pericytes and myofibroblasts are essential for lung development, through their roles in vascularisation and alveolarisation, respectively. The G proteins Gαq and Gα11 (Gαq/11 ) are key components of physiological and pathophysiological signalling pathways, but the role of mesenchymal Gαq/11 signalling in lung development is unknown. Methods: Gαq floxed, Gα11 knockout homozygous mice (Gnaq fl/fl ;Gna11 -/- ) were crossed with Pdgfrb-Cre ± mice to generate offspring lacking Gαq/11 in Pdgfrb-expressing cells (pericytes, myofibroblasts). Organs were harvested from 2 week old mice for histological and biochemical analyses. Whole lung RNA from Gαq/11 -deficient and control mice was analysed using Clariom TM D Mouse microarray chips (Affymetrix) and Partek Genomics Suite 6.6 software. Differentially expressed genes were considered of interest with p≤0.05 and fold change ±1.5. Results: Mesenchymal Gαq/11 -knockout mouse lungs had enlarged airspaces, thickened alveolar walls, fewer secondary septae, and fewer elastin fibres on histology compared with controls (p<0.05, n=4), demonstrating abnormal alveolarisation. Additionally, thickened peripheral pulmonary vessels in mesenchymal Gαq/11 -knockout lungs indicated a pulmonary vascular abnormality. Whole lung RNA microarray demonstrated downregulation of mt-Tk, a key mitochondrial function gene, and several miRNAs known to regulate angiogenesis, proliferation, and cellular differentiation (miR-684, miRlet7f-1, miR186) in mesenchymal Gαq/11 -knockout lungs compared with controls (p<0.05, fold change >1.5). High gene expression variability in mesenchymal Gαq/11 -knockout lungs may indicate variations in phenotype, and these findings require validation. Neoplastic hyperproliferation of the medullary tubular epithelium in mice lacking mesenchymal Gαq/11 was found on renal histology, suggesting a role for mesenchymal Gαq/11 in tumour suppression. Conclusion: Gαq/11 signalling in Pdgfrb-positive cells is essential for normal lung development, with regulation of elastin deposition, mitochondrial function, angiogenesis, and proliferation as candidate mechanisms. Mesenchymal Gαq/11 signalling regulates renal epithelial proliferation, highlighting a shared developmental and malignant pathway. This is the first study to generate mesenchymal Gαq/11 -knockout mice, further investigation of which may identify therapeutic targets for developmental lung disease.